Experimental Economics : How We can Build Better Financial Markets - Miller, Ross M.; Foreword by Vernon L. Smith (Hoboken, New Jersey John Wiley & Sons, 2002)
An account of the new developments in economics: the scientific roots of modern finance and modern financial institutions; and the complex economic principles that govern our world of finance--P. [4] of cover.
Include Notes, Bibliography and Index
Keywords: Stock exchanges. -- Options (Finance)